2020
DOI: 10.1016/j.jechem.2020.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical study of different membrane materials for the fabrication of stable, reproducible and reusable reference electrode

Abstract:  Fabrication of a reference electrode Ni/Ni(OH)2 from eutectic molten hydroxides.  Eutectic molten hydroxide (NaOH-KOH, 49-51 mol%) at temperature 300 o C was used.  Stability and reusability of electrode covered by mullite and alumina tube. Cyclic voltammetry analyses were carried out to authenticate the results. Stability and reusability of the novel electrode was checked for 9 and 3 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 36 publications
4
38
0
Order By: Relevance
“…This improved the removal rate and also reduced the amount of liquid material re-to the surface. Kunieda et al [23] and Singh et al [27] have also reported similar findings.…”
Section: Response Surface Of Mrrsupporting
confidence: 55%
See 1 more Smart Citation
“…This improved the removal rate and also reduced the amount of liquid material re-to the surface. Kunieda et al [23] and Singh et al [27] have also reported similar findings.…”
Section: Response Surface Of Mrrsupporting
confidence: 55%
“…Researchers have also explored the use of different novel reference electrodes in various processes [22][23]. The finding indicated that novel electrodes have a positive impact on the performance of the process.…”
Section: Introductionmentioning
confidence: 99%
“…The molten hydroxide salt is preferred in the case of hydrogen production leading to hydrocarbons formation. Hydrocarbon molecules can be formed basically through a H2 reaction with either C or CO as the same mechanism for molten chlorides 49 . In most experiments using molten hydroxides, the conversion of CO2 was very high but the hydrocarbon yields were still low.…”
Section: Molten Hydroxide Electrolytementioning
confidence: 99%
“…Since Boddy et al reported the first scientific case on water splitting by using n-type semiconductor TiO 2 as anode material in 1968 [3], many researchers have been devoted to the study of hydrogen production by water splitting [4][5][6][7][8][9]. Conventional hydrogen production methods are mainly based on fossil-fuel technology, such as steam reforming [9], partial oxidation and coal gasification [10,11], which are not sustainable and usually lead to heavily CO 2 emission. Besides, nuclear energy [12] and thermogravimetry analyzer (TGA) [13] technologies both can be used to produce hydrogen.…”
Section: Introductionmentioning
confidence: 99%